Lower‐ and Higher‐Order Nonclassical Properties of Photon Added and Subtracted Displaced Fock States. Issue 2 (10th January 2019) - Malpani, Priya; Alam, Nasir; Thapliyal, Kishore; Pathak, Anirban; Narayanan, V.; Banerjee, Subhashish
Abstract: Nonclassical properties of photon added and subtracted displaced Fock states are studied using various witnesses of lower‐ and higher‐order nonclassicality. Compact analytic expressions are obtained for the nonclassicality witnesses. Using those expressions, it is established that these states and the states that can be obtained as their limiting cases (except coherent states) are highly nonclassical as they show the existence of lower‐ and higher‐order antibunching and sub‐Poissonian photon statistics, in addition to the nonclassical features revealed through the Mandel Q M parameter, zeros of Q function, Klyshko's criterion, and Agarwal–Tara criterion. Further, some comparison between the nonclassicality of photon added and subtracted displaced Fock states have been performed using witnesses of nonclassicality. This has established that between the two types of non‐Gaussianity inducing operations (i.e., photon addition and subtraction) used here, photon addition influences the nonclassical properties more strongly. Further, optical designs for the generation of photon added and subtracted displaced Fock states from squeezed vacuum state have also been proposed. Abstract : A comparative study of the nonclassicality present in photon added and subtracted displaced Fock states shows photon addition is generally preferable nonclassicality inducing operation, while photon subtraction has an advantage in some cases over photon addition. Various lower‐order and higher‐order nonclassical features are found to be present in these states.